Influence of colourants on environmental degradation of plastic litter - Sarah Key; Peter G. Ryan; Sarah E. Gabbott; Jack Allen; Andrew P. Abbott (Environmental Pollution, 2024)

Siderophore production and utilization by marine bacteria in the North Pacific Ocean - Jiwoon Park; Bryndan P. Durham; Rebecca S. Key; Ryan D. Groussman; Zinka Bartolek; Paulina Pinedo‐Gonzalez; Nicholas J. Hawco; Seth G. John; Michael C. G. Carlson; Debbie Lindell; Lauren W. Juranek; Sara Ferrón; et al. (Limnology and Oceanography, 2023)
Siderophores are strong iron‐binding molecules produced and utilized by microbes to acquire the limiting nutrient iron (Fe) from their surroundings. Despite their importance as a component of the iron‐binding ligand pool in seawater, data on the distribution of siderophores and the microbes that use them are limited. Here, we measured the concentrations and types of dissolved siderophores during two cruises in April 2016 and June 2017 that transited from the iron‐replete, low‐macronutrient North Pacific Subtropical Gyre through the North Pacific Transition Zone (NPTZ) to the iron‐deplete, high‐macronutrient North Pacific Subarctic Frontal Zone (SAFZ). Surface siderophore concentrations in 2017 were higher in the NPTZ (4.0–13.9 pM) than the SAFZ (1.2–5.1 pM), which may be partly attributed to stimulated siderophore production by environmental factors such as dust‐derived iron concentrations (up to 0.51 nM). Multiple types of siderophores were identified on both cruises, including ferrioxamines, amphibactins, and iron‐free forms of photoreactive siderophores, which suggest active production and use of diverse siderophores across latitude and depth. Siderophore biosynthesis and uptake genes and transcripts were widespread across latitude, and higher abundances of these genes and transcripts at higher latitudes may reflect active siderophore‐mediated iron uptake by the local bacterial community across the North Pacific. The variability in the taxonomic composition of bacterial communities that transcribe putative ferrioxamine, amphibactin, and salmochelin transporter genes at different latitudes further suggests that the microbial groups involved in active siderophore production and usage change depending on local conditions.

Clustering of KOR PET images separates people with AUD into distinct responses to naltrexone - Jocelyn Hoye; Jose Key; Bart de Laat; Kelly P. Cosgrove; Suchitra Krishnan-Sarin; Xenophon Papademetris; Evan D. Morris (Brain Imaging and Behavior, 2023)

Glycine betaine uptake and metabolism in marine microbial communities - Angela K. Boysen; Bryndan P. Durham; William Kumler; Rebecca S. Key; Katherine R. Heal; Laura T. Carlson; Ryan D. Groussman; E. Virginia Armbrust; Anitra E. Ingalls (Environmental Microbiology, 2022)
Summary Glycine betaine (GBT) is a compatible solute in high concentrations in marine microorganisms. As a component of labile organic matter, GBT has complex biochemical potential as a substrate for microbial use that is unconstrained in the environment. Here we determine the uptake kinetics and metabolic fate of GBT in two natural microbial communities in the North Pacific characterized by different nitrate concentrations. Dissolved GBT had maximum uptake rates of 0.36 and 0.56 nM h −1 with half‐saturation constants of 79 and 11 nM in the high nitrate and low nitrate stations respectively. During multiday incubations, most GBT taken into cells was retained as a compatible solute. Stable isotopes derived from the added GBT were also observed in other metabolites, including choline, carnitine and sarcosine, suggesting that GBT was used for biosynthesis and for catabolism to pyruvate and ammonium. Where nitrate was scarce, GBT was primarily metabolized via demethylation to glycine. Gene transcript data were consistent with SAR11 using GBT as a source of methyl groups to fuel the methionine cycle. Where nitrate concentrations were higher, more GBT was partitioned for lipid biosynthesis by both bacteria and eukaryotic phytoplankton. Our data highlight unexpected metabolic pathways and potential routes of microbial metabolite exchange.

Kinematic and Somatosensory Gains in Infants with Cerebral Palsy After a Multi-Component Upper-Extremity Intervention: A Randomized Controlled Trial - Nathalie L. Maitre; Arnaud Jeanvoine; Paul J. Yoder; Alexandra P. Key; James C. Slaughter; Helen Carey; Amy Needham; Micah M. Murray; Jill Heathcock; Stephanie Burkhardt; Lelia Emery; Kaleigh Hague; et al. (Brain Topography, 2020)

Neonatal Multisensory Processing in Preterm and Term Infants Predicts Sensory Reactivity and Internalizing Tendencies in Early Childhood - Nathalie L. Maitre; Alexandra P. Key; James C. Slaughter; Paul J. Yoder; Mary Lauren Neel; Céline Richard; Mark T. Wallace; Micah M. Murray (Brain Topography, 2020)
Multisensory processes include the capacity to combine information from the different senses, often improving stimulus representations and behavior. The extent to which multisensory processes are an innate capacity or instead require experience with environmental stimuli remains debated. We addressed this knowledge gap by studying multisensory processes in prematurely born and full-term infants. We recorded 128-channel event-related potentials (ERPs) from a cohort of 55 full-term and 61 preterm neonates (at an equivalent gestational age) in response to auditory, somatosensory, and combined auditory-somatosensory multisensory stimuli. Data were analyzed within an electrical neuroimaging framework, involving unsupervised topographic clustering of the ERP data. Multisensory processing in full-term infants was characterized by a simple linear summation of responses to auditory and somatosensory stimuli alone, which furthermore shared common ERP topographic features. We refer to the ERP topography observed in full-term infants as “typical infantile processing” (TIP). In stark contrast, preterm infants exhibited non-linear responses and topographies less-often characterized by TIP; there were distinct patterns of ERP topographies to multisensory and summed unisensory conditions. We further observed that the better TIP characterized an infant’s ERPs, independently of prematurity, the more typical was the score on the Infant/Toddler Sensory Profile (ITSP) at 12 months of age and the less likely was the child to the show internalizing tendencies at 24 months of age. Collectively, these results highlight striking differences in the brain’s responses to multisensory stimuli in children born prematurely; differences that relate to later sensory and internalizing functions.

Comparative Toxicity of Two Chemical Dispersants and Dispersed Oil in Estuarine Organisms - M. E. DeLorenzo; P. B. Key; K. W. Chung; E. Pisarski; B. Shaddrix; E. F. Wirth; P. L. Pennington; J. Wade; M. Franco; M. H. Fulton (Archives of Environmental Contamination and Toxicology, 2018)

Somatosensory Event-Related Potentials and Association with Tactile Behavioral Responsiveness Patterns in Children with ASD - Carissa J. Cascio; Chang Gu; Kimberly B. Schauder; Alexandra P. Key; Paul Yoder (Brain Topography, 2015)

Relationship between land use classification and grass shrimp Palaemonetes spp. population metrics in coastal watersheds - James W. Daugomah; P. B. Key; J. B. West; N. R. Shea; S. McDaniel; P. L. Pennington; M. H. Fulton (Environmental Monitoring and Assessment, 2014)

Interactive Effects of Mosquito Control Insecticide Toxicity, Hypoxia, and Increased Carbon Dioxide on Larval and Juvenile Eastern Oysters and Hard Clams - R. N. Garcia; K. W. Chung; P. B. Key; L. E. Burnett; L. D. Coen; M. E. DeLorenzo (Archives of Environmental Contamination and Toxicology, 2014)

Physical activity, sex steroid, and growth factor concentrations in pre- and post-menopausal women: a cross-sectional study within the EPIC cohort - S. Rinaldi; R. Kaaks; C. M. Friedenreich; T. J. Key; R. Travis; C. Biessy; N. Slimani; K. Overvad; J. N. Østergaard; A. Tjønneland; A. Olsen; S. Mesrine; et al. (Cancer Causes & Control, 2014)

Paleoenvironmental reconstruction of the Early to Middle Miocene Central Paratethys using stable isotopes from bryozoan skeletons - Marcus M. Key; Kamil Zágoršek; William P. Patterson (International Journal of Earth Sciences, 2013)

Recent range expansions in non-native predatory beetles on sub-Antarctic South Georgia - P. Convey; R. S. Key; R. J. D. Key; M. Belchier; C. L. Waller (Polar Biology, 2011)

Fruits and vegetables consumption and the risk of histological subtypes of lung cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) - F. L. Büchner; H. B. Bueno-de-Mesquita; J. Linseisen; H. C. Boshuizen; L. A. L. M. Kiemeney; M. M. Ros; K. Overvad; L. Hansen; A. Tjonneland; O. Raaschou-Nielsen; F. Clavel-Chapelon; M.-C. Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Effects of chemically spiked sediments on estuarine benthic communities: a controlled mesocosm study - W. L. Balthis; J. L. Hyland; M. H. Fulton; P. L. Pennington; C. Cooksey; P. B. Key; M. E. DeLorenzo; E. F. Wirth (Environmental Monitoring and Assessment, 2010)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

An evaluation of contaminated estuarine sites using sediment quality guidelines and ecological assessment methodologies - M. Fulton; P. Key; E. Wirth; A. K. Leight; J. Daugomah; D. Bearden; S. Sivertsen; G. Scott (Ecotoxicology, 2006)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

Surface Water Pesticide Movement from the Dade County Agricultural Area to the Everglades and Florida Bay via the C-111 Canal - M. H. Fulton; G. I. Scott; M. E. DeLorenzo; P. B. Key; D. W. Bearden; E. D. Strozier; C. J. Madden (Bulletin of Environmental Contamination and Toxicology, 2004)

Acetylcholinesterase Activity in Grass Shrimp and Aqueous Pesticide Levels from South Florida Drainage Canals - P. B. Key; M. H. Fulton; J. A. Harman-Fetcho; L. L. McConnell (Archives of Environmental Contamination and Toxicology, 2003)

Toxicity of the Insecticides Fipronil and Endosulfan to Selected Life Stages of the Grass Shrimp ( Palaemonetes pugio ) - P. B. Key; K. W. Chung; A. D. Opatkiewicz; E. F. Wirth; M. H. Fulton (Bulletin of Environmental Contamination and Toxicology, 2003)

Microsatellite markers for investigating population structure in Octopus vulgaris (Mollusca: Cephalopoda) - E. C. Greatorex; C. S. Jones; J. Murphy; L. N. Key; A. M. Emery; P. R. Boyle (Molecular Ecology, 2000)

Toxicity of Sediment Associated PAHs to the Estuarine Crustaceans, Palaemonetes pugio and Amphiascus tenuiremis - E. F. Wirth *, M. H. Fulton; G. T. Chandler; P. B. Key; G. I. Scott (Bulletin of Environmental Contamination and Toxicology, 1998)

Azinphosmethyl Exposure to Grass Shrimp ( Palaemonetes pugio ) Life Stages with Emphasis on Larval Acetylcholinesterase Activity - P. B. Key; M. H. Fulton; S. L. Layman; G. I. Scott (Bulletin of Environmental Contamination and Toxicology, 1998)

In Situ Monitoring of Dredged Material Spoil Sites Using the Oyster Crassostrea virginica - E. F. Wirth; G. I. Scott; M. H. Fulton; R. F. Van Dolah, P. P. Maier, N. Hadle; P. B. Key (Archives of Environmental Contamination and Toxicology, 1996)

In situ monitoring of dredged material spoil sites using the oyster Crassostrea virginica - E. F. Wirth; G. I. Scott; M. H. Fulton; R. F. Van Dolah; P. P. Maier; N. Hadley; J. W. Daugomah; P. B. Key (Archives of Environmental Contamination and Toxicology, 1996)

Basic nuclear proteins in the Omycete fungus Achlya bisexualis - P. A. Horgen; R. T. Nagao; L. S. Y. Chia; J. L. Key (Archives of Microbiology, 1973)